Alternative technique in atypical spinal decompression: the use of the ultrasonic scalpel in paediatric achondroplasia. (10th June 2016) - Woodacre, Timothy; Sewell, Matthew; Clarke, Andrew J; Hutton, Mike
Abstract : Spinal stenosis can be a very disabling condition. Surgical decompression carries a risk of dural tear and neural injury, which is increased in patients with severe stenosis or an atypical anatomy. We present an unusual case of symptomatic stenosis secondary to achondroplasia presenting in a paediatric patient, and highlight a new surgical technique used to minimise the risk of dural and neural injury during decompression.